Implementation of Nutrition-Based Culinary Education for Community Welfare through Demonstration and Active Participation Methods - Daniel Pandu Mau; Ivy Dian Puspitasari Prabowo; Elvin Adisatria Lukman; Yohanes Elijah Loo; Lionel Messi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Enhancing community knowledge regarding healthy cooking techniques and nutrition was an important need. This activity sought to provide nutrition-based culinary education through demonstration methods and active participant involvement. The methods employed involved direct instructor demonstrations and evaluations using questionnaires and in-depth interviews. The evaluation results indicated a high level of participant satisfaction, with 86.4% expressing satisfaction with the materials, 82.6% appreciating the demonstration methods, and 89.1% being satisfied with the instructors' capabilities. Further interviews confirmed that many participants felt more confident applying healthy cooking techniques at home, with the professional and friendly instructors receiving high praise. The discussion highlighted the importance of interactive methods in enhancing understanding and recommended including health-related topics and using local ingredients in future programs. The conclusion indicated that this culinary education program encouraged participants to adopt healthier eating habits. Recommendations for further development included enhancing materials with additional topics and incorporating hands-on cooking practice sessions to strengthen participants' skills.